Fred's Med Frederick Ashton's Ondine reassessed - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Frederick Ashton's Ondine reassessed. There are some who only seem to want to see Fonteyn recreated, I would be very happy to see a new approach: it's a strong role, and there's no reason why there shouldn't be as many different Ondines as there are Giselles. PALABRAS CLAVE: Frederick Ashton, Ondine, Hans Werner Henze, Royal Ballet, Anthony Dowell, Fonteyn.